Item response analysis of the academic self-efficacy scale (TASES) Indonesian version with GPCM - Luh Bella Elistya Widiana; Ananta Yudiarso; Foebe Imantaka Iswahyudi; Rangga Saputra (Mathematics Education Study Program, 2025)
There have been many studies developed to measure student self-efficacy. One of the instruments developed is the academic self-efficacy scale (TASES) designed by Sagone & Caroli (2014). The TASES instrument has four dimensions, namely, self-engagement, self-oriented decision making, others-oriented problem solving, and interpersonal climate. There were 30 items in the original version, but after being analyzed only 28 items remained. When adapted and validated in the Indonesian version, the remaining items are 25 items. This study aims to analyze item responses using the 2PL generalized partial credit model (GPCM) method. The participants involved in the research were 242 college students aged 18-25 years who were migrating outside the city or outside the island to pursue higher education. The results show that there are six items that have low discriminatory power (<0.4) so that they need to be revised (i9, i11, i24, i25, and i28) or eliminated (i12 and i24). In addition, the value of Cronbach's alpha on the interpersonal climate dimension is <0.7 so that it can be said to have poor consistency in measuring the self-efficacy of overseas students.